Development of Flipbook Teaching Materials on Earth Surface Changes to Improve Learning Outcomes of Fifth Grade Elementary School Students - Ariani, Alvida; Wenda, Dhian Dwi Nur; Kurnia, Ita (Lembaga KITA, 2025)
This study was motivated by existing issues at SDN Tarokan 4. Based on the results of interviews, classroom observations, and an analysis of students’ learning outcomes by the grade V teacher, it was found that there was a lack of variety in teaching materials and suboptimal use of technology in the classroom. Out of 41 students, only 13 achieved scores above the Minimum Learning Mastery Criteria (KKTP) in the topic of changes to the Earth's surface. To address these issues, a flipbook-based teaching material was developed to improve student learning outcomes. The aim of this research is to determine the validity, practicality, and effectiveness of the developed flipbook teaching material. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The trial subjects comprised 41 students, with 10 participating in the limited trial and 31 in the broader trial. Instruments used included validation sheets, teacher and student response questionnaires, as well as pretest and posttest assessments. Validation results from subject matter experts and teaching material experts indicated that the product falls under the “highly valid” category, with an average percentage of 93%. Practicality analysis based on teacher response questionnaires in the limited trial showed a percentage of 100%, while student response questionnaires in the broader trial yielded a percentage of 82.5%. Both are categorized as “highly practical.” Meanwhile, the effectiveness of the teaching material was demonstrated through the N-gain test, which showed a 77.07% increase between pretest and posttest scores, classified as “effective.” Based on these results, the flipbook teaching material is deemed suitable for use in teaching the topic of changes to the Earth's surface to improve learning outcomes for grade V elementary students.